The four stages of the knowledge sharing process in SMEs. (20th April 2020) - Anand, Amitabh; Walsh, Isabelle
This paper takes an exploratory and qualitative stance to investigate and understand how employees within SMEs share their knowledge in a dyadic situation. The research is set in an Indian context. Through participant observation and interviews with both supervisors and employees, we unmask the four essential stages of the dyadic process through which knowledge sharing occurs: identification, medium selection, engagement, and feedback. Based on our findings, we highlight theoretical and practical implications for SME business leaders.